MARGINALIZATION OF BEDEKEH RITUAL PERFORMED BY AKIT ETHNIC GROUP IN RUPAT ISLAND, BENGKALIS REGENCY, RIAU PROVINCE IN THE ERA OF GLOBALIZATON - Suroyo, Suroyo; Kumbara, Anak Agung Ngurah Anom; Suarka, I Nyoman; MPSS, Pudentia (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2017)
This present study is intended to explore, identify, comprehend and describe the phenomenon of the bedekeh ritual performed by the Akit ethnic group in Riau Island, Bengkalis Regency, Riau Province in the era of globalization. The Oang Akit (those who belong to the Akit ethnic group) believe that all diseases are believed to result from the interference of invisible spirits or what is locally referred to as Antu (Hantu=Ghost), their ancestors, the treatment of other people or what is referred to as disantet (black magic practice), and curses. The bedekeh ritual is a cultural important element; it is not only performed to stimulate emotion but it is also performed to make the relationship among people and between people and the cosmos in harmony. Globalization has developed human life and changed the people’s way of life, including the Akit ethnic group. The data in the present study were collected using the techniques of observation, in-depth interview, library research, and documentation. Based on what was explored and the method used to analyze the data, it was found that the bedekeh tradition is still performed by the Akit ethnic group; however, its existence is getting marginalized by the internal and external factors. The modern epistemology (Modern-Western) in which rationality is considered more important than other things has caused the therapy performed by the Akit ethnic group to shift. Hegemony resulting from the penetration of the culture belonging to the non Akit ethnic groups has also caused the bedekeh ritual to be marginalized.